Magnetic Induction Tomography using Vector Spherical Harmonic Magnetic Fields and Quantum Sensing - Perarulalan, Nandhakishore (2025)
The work explores the use of spherical harmonic magnetic vector fields in magnetic induction tomography, an eddy current based non-ionising imaging technique. It uses the spherical harmonic magnetic fields as primary excitor fields, creating orthogonal sensitivity matrices ensuring efficient and accurate image reconstruction using two different algorithms. The thesis further explores the phase of the eddy current induced secondary magnetic fields and seeks to use phase in image reconstruction. Lastly, the thesis seeks to measure the eddy current induced secondary magnetic fields from low conductivity materials using quantum sensors known as optically pumped magnetometers.